2014
DOI: 10.1101/012914
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The pig X and Y chromosomes: structure, sequence and evolution

Abstract: We have generated an improved assembly and gene annotation of the pig X chromosome, and a first draft assembly of the pig Y chromosome, by sequencing BAC and fosmid clones, and incorporating information from optical mapping and fibre-FISH. The X chromosome carries 1,014 annotated genes, 689 of which are protein-coding. Gene order closely matches that found in Primates (including humans) and Carnivores (including cats and dogs), which is inferred to be ancestral. Nevertheless, several protein-coding genes prese… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 83 publications
(92 reference statements)
0
7
0
Order By: Relevance
“…We did not detect massive amplification of gene families as observed on mammalian sex chromosomes Murphy et al 2006;Hughes et al 2010;Paria et al 2011;Soh et al 2014; Janečka numbers we observed are on the same order as the duplicated genes on the sex chromosomes 519 of multiple species of Drosophila (Chang and Larracuente 2018;Ellison and Bachtrog 2019). The 520 gene duplications on the threespine stickleback sex chromosomes may reflect selection on the 521 early amplification of genes important for male fertility (Gvozdev et al 2005) or to prevent 522 degradation by providing a repair template through gene conversion (Rozen et al 2003;Skaletsky 523 et al 2003;Backström et al 2005;Bhowmick et al 2007;Connallon and Clark 2010;Davis et al 524 2010;Marais et al 2010;Hallast et al 2013;Soh et al 2014;Skinner et al 2016;Peneder et al 525 2017;Trombetta and Cruciani 2017;Chang and Larracuente 2018). Alternatively, the duplications 526 we observe on the threespine stickleback Y chromosome may simply reflect recent translocations 527 and duplications that have yet to degenerate and pseudogenize.…”
mentioning
confidence: 53%
“…We did not detect massive amplification of gene families as observed on mammalian sex chromosomes Murphy et al 2006;Hughes et al 2010;Paria et al 2011;Soh et al 2014; Janečka numbers we observed are on the same order as the duplicated genes on the sex chromosomes 519 of multiple species of Drosophila (Chang and Larracuente 2018;Ellison and Bachtrog 2019). The 520 gene duplications on the threespine stickleback sex chromosomes may reflect selection on the 521 early amplification of genes important for male fertility (Gvozdev et al 2005) or to prevent 522 degradation by providing a repair template through gene conversion (Rozen et al 2003;Skaletsky 523 et al 2003;Backström et al 2005;Bhowmick et al 2007;Connallon and Clark 2010;Davis et al 524 2010;Marais et al 2010;Hallast et al 2013;Soh et al 2014;Skinner et al 2016;Peneder et al 525 2017;Trombetta and Cruciani 2017;Chang and Larracuente 2018). Alternatively, the duplications 526 we observe on the threespine stickleback Y chromosome may simply reflect recent translocations 527 and duplications that have yet to degenerate and pseudogenize.…”
mentioning
confidence: 53%
“…Despite its importance, the sequence of the Y Chromosome has so far been determined only for a handful of mammals-human, chimpanzee, rhesus macaque, mouse, and pig Hughes et al 2010Hughes et al , 2012aSoh et al 2014;Skinner et al 2016), as well as partially sequenced for bull, dog, cat, marmoset, opossum, and rat (Chang et al 2013;Li et al 2013;Bellott et al 2014).…”
mentioning
confidence: 99%
“…Moreover, many mammalian genome projects have focused on females to obtain reliable X chromosome sequences (Hughes et al 2012). As a consequence, the complete sequences of Y chromosome have only been determined for a handful of mammals, such as humans (Homo sapiens) (Skaletsky et al 2003), chimpanzees (Pan troglodytes) (Hughes et al 2010), rhesus macaques (Macaca mulatta) (Hughes et al 2012), gorillas (Tomaszkiewicz et al 2016) (Western lowland gorilla), pigs (Sus scrofa) (Skinner et al 2016) and mice (Mus musculus) (Soh et al 2014), as well as partially sequenced for cattle (Bos taurus) (Chang et al 2013), dogs (Canis lupus familiaris), cats (Felis catus) (Li et al 2013), polar bears (Ursus maritimus) (Bidon et al 2015), horse (Equus caballus) (Wallner et al 2017), marmosets (Callithrix jacchus), opossums (Monodelphis domestica) and rats (Rattus norvegicus) (Bellott et al 2014).…”
Section: Introductionmentioning
confidence: 99%